With a little help from my friends: supported self-employment for people with severe disabilities. - Rizzo DC (Journal of Vocational Rehabilitation, 2002)
People with disabilities are utilizing self-employment as a work option in greater numbers than ever before. However, there has not been a concerted look at methods or practices which may open the option of self-employment for those with severe disabilities or severe support needs. While the unemployment rate for people with severe disabilities remains at around 70%, work. The option of self-directed employment does exist and, according to a review of both social supports and business supports, can be practically applied. Employment efforts that intelligently combine business support systems with personal social support systems more typical for people with severe disabilities can open the option of self-employment and self-directed employment for this group. Future exploration and testing of methods is also discussed.